Efeito de sete semanas de preparação integrada para atletas de futebol da categoria sub20 - Grandim, G.; Germano, M. D.; Lovaglio Belozo, F.; Prestes, J.; Lopes, C. R. (Revista Brasileira de Ciência e Movimento, 2016)
The aim of this study was to investigate the effect of seven weeks of training through integrated training for neuromuscular and metabolic abilities of soccer players. The study included 20 male soccer field players high-performance they competed in the U-20 Paulista Championship of a professional team from São Paulo, aged 19,1±0,8 years, body mass 71,6± 6,5 kg, height 1,8±0,1 cm. The results show a increase in body mass (71,6±6,5 pre vs. post 72,4±6,4 kg) and lean body mass (62,2±5,3 pre vs. post 63,2±5,0 kg) after seven weeks of training (p<0,05). It was observed increase in vertical jump height (36,7±3,7 pre vs. post 38,1±5,1 cm) and power (pré 47,6±3,1 vs. pós 48,9±4,7 W·kg-1) through the Squat Jump, and height (43,5±4,1 pre vs. post 44,7±4,8 cm) and power (pré 53,5±3,5 vs. pós 54,2±4,3 W·kg-1) of countermovement jump (p<0.05). In addition it was observed an increase in velocity by means of a reduction in time sprints (15 m) (3,0±0,1 pre vs. post 2,7±0,1 s) (p<0.05). In anaerobic endurance was observed improvement in repeated sprint fatigue index (10,5±2,6 pre vs. post 8,5±1,6%), and average time of repeated sprints (5,2±0,2 pre vs. post 5,1±0,2 s) (p<0.05). Aerobic resistance was found improvement in VO2max (47,6±2,8 pre vs. post 48,7±2,5 ml/kg/min), the distance traveled (1334,0±335,0 pre vs. post 1468,0±305,2 m) (p<0.05). Finally, it found improvement in maximum strength by the 1-RM test in the exercise squats (88,0±16,1 pre vs. post 122,1±17,7 kg) (p<0.05). The organization of periodization training program provided increment in specific soccer physical abilities and improve anthropometric parameters in short preseason time.